2015
DOI: 10.1021/acs.jpcb.5b03274
|View full text |Cite
|
Sign up to set email alerts
|

A Few Case Studies on the Correlation of Particle Network and Its Stability on the Ionic Conductivity of Solid–Liquid Composite Electrolytes

Abstract: We discuss here the crucial role of the particle network and its stability on the long-range ion transport in solid-liquid composite electrolytes. The solid-liquid composite electrolytes chosen for the study here comprise nanometer sized silica (SiO2) particles having various surface chemical functionalities dispersed in nonaqueous lithium salt solutions, viz. lithium perchlorate (LiClO4) in two different polyethylene glycol based solvents. These systems constitute representative examples of an independent cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…51 The existence of better particle networks leads to the presence of effective ion transport paths and facilitates ion transport, resulting in the enhancement of ion conductivity. 14 Compared with insulating particles, high-conductivity SC-HC-TiO 2 (HC-TiO 2 ) is free of blocking junctions, and the surface region of the particles can act as an extra pathway for ion conduction, improving ionic conductivity. It is speculated that the charge and ion transport in two different phases and across several solid/liquid interfaces in a high-conductivity system may involve electronic exchange-based ion transport.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…51 The existence of better particle networks leads to the presence of effective ion transport paths and facilitates ion transport, resulting in the enhancement of ion conductivity. 14 Compared with insulating particles, high-conductivity SC-HC-TiO 2 (HC-TiO 2 ) is free of blocking junctions, and the surface region of the particles can act as an extra pathway for ion conduction, improving ionic conductivity. It is speculated that the charge and ion transport in two different phases and across several solid/liquid interfaces in a high-conductivity system may involve electronic exchange-based ion transport.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the composite electrolytes composed of SC-TiO 2 in the ionic liquid, NH 2 groups on SC-TiO 2 interact via hydrogen bonding either with ionic liquid molecules or with the NH 2 groups of adjacent oxide particles, resulting in the spanning attractive regularized particle networks . The existence of better particle networks leads to the presence of effective ion transport paths and facilitates ion transport, resulting in the enhancement of ion conductivity . Compared with insulating particles, high-conductivity SC-HC-TiO 2 (HC-TiO 2 ) is free of blocking junctions, and the surface region of the particles can act as an extra pathway for ion conduction, improving ionic conductivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the free counter ions are formed at the space charge region at the interfaces between oxide particles and liquid electrolytes. When the particles are close to each other or when they overlap, percolations in ionic conductivity are generated . However, the nanoparticles have high potential for aggregation that can obstruct the ion transportation on the TiO 2 in DSSCs electrodes because the two sub‐phases are separated .…”
Section: Introductionmentioning
confidence: 99%
“…Several reports investigated the addition of inorganic fillers, such as silica (SiO 2 ), copper oxide (CuO), and titania (TiO 2 ) particles, into liquid or polymer electrolytes to enhance the conductivity and thermal stability. Bhattacharyya et al found that the addition of specific amounts of oxide particles (SiO 2 and TiO 2 ) to organic solvent-based (liquid) electrolytes enhanced the conductivities of the composites relative to the pure liquid electrolytes. This phenomenon was explained using heterogeneous percolation theories at the interfaces .…”
Section: Introductionmentioning
confidence: 99%